2018
DOI: 10.1073/pnas.1809028115
|View full text |Cite
|
Sign up to set email alerts
|

Role of humoral immunity against hepatitis B virus core antigen in the pathogenesis of acute liver failure

Abstract: Hepatitis B virus (HBV)-associated acute liver failure (ALF) is a dramatic clinical syndrome leading to death or liver transplantation in 80% of cases. Due to the extremely rapid clinical course, the difficulties in obtaining liver specimens, and the lack of an animal model, the pathogenesis of ALF remains largely unknown. Here, we performed a comprehensive genetic and functional characterization of the virus and the host in liver tissue from HBV-associated ALF and compared the results with those of classic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 69 publications
4
73
1
Order By: Relevance
“…24,25 In addition, some patients harbor HBcAg-specific B cell clones that can induce acute cell-lysis through a T cellindependent antibody-complement mediated mechanism. 26,27 Future mechanistic studies should therefore aim at clarifying the putative pathogenic potential of HBcAg-specific B cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 In addition, some patients harbor HBcAg-specific B cell clones that can induce acute cell-lysis through a T cellindependent antibody-complement mediated mechanism. 26,27 Future mechanistic studies should therefore aim at clarifying the putative pathogenic potential of HBcAg-specific B cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining in severe AHB showed that at week 6 there was an infiltration of CD20-positive B cells distributed as single cells within the lobule, which increased at week 11, after the ALT peak, when they also appeared as aggregates in the portal areas ( Fig 3A and 3B), whilst in classic AHB, at the time of the ALT peak, they were rarely detected within the lobule and appeared as small aggregates in the portal tracts ( Fig 3E and 3F) [10]. In severe AHB, we observed some plasma cells positive for Mum-4 and cytoplasmic IgM (S1B Fig).…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Next-generation sequencing (NGS) of HBV strains isolated from the liver of patients with HBV ALF showed a highly mutated HBcAg with the precore stop codon mutation present in 100% of the viral population. Thus, our previous study delineates ALF as an anomalous HBV core-driven B-cell disease [10], which results from the encounter between a highly mutated HBcAg and an unusual B-cell response.…”
Section: Introductionmentioning
confidence: 97%
“…Fulminant hepatitis can be associated with an overwhelming B cell response specific for the HBcAg in HBeAg-negative HBV acute infection 15,16. (6) The propensity to develop precore and core promoter mutations that affect HBeAg expression is influenced by genotype/subgenotype, which is associated with clinical outcomes 17.…”
mentioning
confidence: 99%